Yunpi Tongbian Fang alleviates slow transit constipation induced by loperamide by regulating intestinal microbiota and short-chain fatty acids in rats: YPTBF relieves STC through intestinal microflora - Xu, Wenjie; Xu, Shanshan; Feng, Ruobing; Zeng, Li (Cellular and Molecular Biology, 2023)
Slow transit constipation (STC) is a prevalent chronic colonic dysfunction disease that significantly impairs the quality of life for affected individuals. Yunpi Tongbian Fang (YPTBF), a traditional Chinese medicine compound, has demonstrated promising clinical efficacy; however, its underlying mechanism remains elusive. In order to assess the laxative properties of YPTBF, which encompasses the influence on gut microbiota, gut metabolites, gut neurotransmitters, and colon histology, an oral administration of YPTBF was conducted for a duration of two consecutive weeks on STC rats induced by loperamide hydrochloride. The results showed that YPTBF improved the symptoms of STC, alleviated the decrease in total fecal volume and fecal water content caused by loperamide-induced constipation, restored intestinal transport function, and HE staining showed the recovery of pathological damage to the colon mucosa. In addition, YPTBF increased the concentrations of 5-HT and ACHE, while reducing the concentrations of VIP and NO. YPTBF adjusted the diversity and abundance of gut microbiota in STC rats, enabling the recovery of beneficial bacteria and promoting the production of acetic acid, propionic acid, and butyric acid. We found that YPTBF can improve constipation in STC rats, possibly by regulating the intestinal microbiota structure and improving SCFAs metabolism